Islamic Law Review On The Legal Status Of Children Born By A Surrogate Mother - Moh Alfin Rosyidi; Mumtaza Nur Annisa (Syakhsiyah Jurnal Hukum Keluarga Islam, 2026)
This article examines the legal status of children born through surrogate motherhood in Islamic law and Indonesian positive law. It asks how Islamic legal reasoning determines nasab and legal parentage when genetic motherhood, gestational motherhood, and intended parenthood are separated by assisted reproductive technology, and how Indonesian law should protect the child without validating a prohibited reproductive arrangement. The article uses doctrinal legal research, comparative fiqh analysis, maqasid-based reasoning, and normative juridical analysis. Primary sources consist of the Qur'an, hadith, classical and contemporary fiqh, fatwas of Islamic legal institutions, Indonesian statutes and regulations, the Compilation of Islamic Law, and Constitutional Court jurisprudence. Secondary sources include recent scholarship on Islamic bioethics, assisted reproduction, child protection, and surrogacy. The article argues that the dominant Sunni and Indonesian Islamic legal approach rejects surrogacy because it disrupts hifz al-nasl, creates uncertainty over nasab, and introduces a third party into reproduction that should remain within a valid marriage. Indonesian health law also restricts assisted reproduction to a lawful husband and wife and to implantation in the wife from whom the ovum originates. The article contributes a prohibition-protection model. Surrogacy as a contract and medical practice should not be legalized, but the child born from it must not be penalized. Courts and public authorities should protect the child's identity, birth registration, maintenance, custody, and civil interests through child-protection mechanisms, adoption or kafalah-like care, and limited bequest where relevant, while keeping nasab, guardianship, and Islamic inheritance consistent with Islamic legal principles